Characterization of Natural Precious Opal Using Modern Spectroscopic Techniques in Ethiopia: The Case from Delanta, South Wollo - Ejigu, Assamen Ayalew; Ketemu, Desalegn Gezahegn; Endalew, Sisay Awoke; Assen, Wudu Yimer (Journal of Spectroscopy, 2022)
The purpose of this study was to conduct characterization of the Delanta natural opals obtained from different mining sites. Characteristics of opals mined from different geological locality were examined. Six opal samples were collected from the main mining sites found in different localities from Delanta district and characterized using Fourier infrared spectroscopy, scanning electron microscopy, X-ray diffraction, and inductively coupled plasma optical emission spectroscopy characterization techniques. The scanning electron microscope micrographs showed that all the samples have relatively semi-ordered (semi-crystalline) structural surface morphologies composed of tiny spherical particles. The performed X-ray diffraction analysis showed that the samples have main peaks at 20.0°, 21.72°, 36.9°, 44.0°, and 56.85° with 2θ values between 10° and 60°. The five diffraction peaks are characteristic peak positions of opal-CT. The Fourier infrared spectroscopy data indicated that the prominent absorption bands for cristobalite at 620 and 520 cm−1 were absent from the spectrum. Instead, three bands in the low frequency region centered at 470, 791, and 1100 cm−1 were observed because of the absorptions of the silicate framework (Si-O) vibrations. red−1−1 Moreover,spectra feature of molecular water and silanol (Si-OH) groups with broadabsorption band centered around 3447 cm-1 andthe O-H stretching vibration of watermolecules and water bending vibration withan absorption band centered around 1634 cm-1were observed.. These values were consistently comparable with literature data. The inductively coupled plasma optical emission spectroscopy analysis showed that four main impurities (>500 parts per million) were Ca (∼1,750–4,730 parts per million), Al (∼1,990–4,319 parts per million, K (∼1,670–3,895 parts per million), and Na (∼595–3,723 parts per million). In general, this study revealed that all opal samples taken from six mining sites in Delanta district were found to be opal-CT as per the results of X-ray diffraction and Fourier infrared spectroscopy investigations.